Conversion of n-Butane to iso-Butene on Gallium/HZSM-5 Catalysts - Gheno,S.M. (2002)
The conversion of n-butane to iso-butene on gallium/HZSM-5 catalysts at 350ºC and WHSV=2.5h8-1 was studied. The catalysts were prepared by ion exchange from a Ga(NO3)2 solution and further submitted to calcination in air at 530ºC. TEM analysis with an EDAX detector and TPR-H2 data showed that after calcination the Ga species were present mainly as Ga2O3, which are reduced to Ga2O at temperatures near 610ºC. The specific acid activity (SAA) of the catalysts increased with the increase in aluminum content in the zeolite, and for a fixed Si/Al ratio, the SAA increased with Ga content. Values for specific hydro/dehydrogenation activity (SH/DHA) were significantly higher than those for SAA, indicating that the catalytic process is controlled by the kinetics on acid sites. Moreover, the production of iso-butene with a selectivity higher than 25% was a evidence that in gallium/HZSM-5-based catalysts the rate of the hydrogenation reaction is lower than that of the dehydrogenation reaction; this behavior confirmed the dehydrogenation nature of gallium species, thereby showing great promise for iso-butene production.